J20 Lattice use in rugby headguards - Woolfenden, Callum (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
This project is related to the design of rugby headguards. The World Rugby regulations limit the ability of headguards to reduce impact force. As such, World Rugby approved headguards are not intended to reduce the risk of serious injuries, like concussion or skull fracture. Rather, current headguards only limit the risk of superficial injuries to the soft tissue, like lacerations and contusions. With concussions linked to CTE (Chronic traumatic encephalopathy), an improvement in headguards could lead to an increased quality of life for all rugby players. With about a quarter of all rugby union injuries being concussion in the 2021/2022 season, there is justification to explore new headguard designs with potential to reduce the risk of such injuries. With World Rugby and the RFL recently introducing new rules for tackle height to try to reduce concussion rates, headguards that offer more protection could also help to reduce concussion rates. A lattice is a structure made from connected cells. When used within protective devices, lattices have potential advantages over the materials traditionally used, such as foams, from reducing the overall mass to allowing forces to be spread more evenly throughout the structure. The aim of this study was to design and comparatively impact test a lattice against foam in relation to rugby headguards. Prior data was limited as most studies on lattices focused on combining materials to have either a hollow lattice or a filled lattice which is not applicable to this study due to World Rugby regulations on protective equipment which states no sandwich material. The FEA results show that the force is more equally distributed through the lattice then it is foam allowing a lower force to hit the base.